Life-cycle of Bothriocephalus claviceps, a specific parasite of eels - Scholz, T (Journal of helminthology, 1997)
The life-cycle of the tapeworm Bothriocephalus claviceps (Goeze, 1782) (Cestoda: Pseudophyllidea), a specific parasite of eels (Anguilla spp.), was studied under experimental conditions. It was demonstrated that the parasite completed its development within 4 months at the temperature range of 22-24 degrees C. Embryonic development was finished in 2 days at this temperature, when coracidia spontaneously hatched. The rate of their development was controlled by water temperature, with delayed formation of coracidia at lower temperatures (8 days at 10-12 degrees C). At 2-4 and 6 degrees C, development did not take place but the eggs remained viable; at 33 degrees C the eggs died. The procercoids developed in copepods of the species Macrocyclops albidus, M. fuscus, Megacyclops viridis, Cyclops strenuus, C. vicinus and Acanthocyclops vernalis (Copepoda: Cyclopidae); their development was finished after 8-12 days at 22-24 degrees C. The definitive hosts, eels, acquired infection after ingestion of infected copepods; the prepatent period of the parasite was more than three months. Perch (Perca fluviatilis) and guppies (Poecilia reticulata) were shown to serve as paratenic hosts of the parasite; in guppies, the tapeworms survived up to 14 days after exposure and they developed similarly to tapeworms in the definitive host.
Keywords: stadia vývoje; Life Cycle Stages; teplota; Anguilla; Animals; Cestode Infections; Temperature; zvířata; cestodózy; Cestoda